2020
DOI: 10.1017/s1047951120001365
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker and conduction disturbances in patients with atrial septal defect

Abstract: AbstractObjective:To determine the prevalence of pacemaker and conduction disturbances in patients with atrial septal defects.Design:All patients with an atrial septal defect born before 1994 were identified in the Danish National Patient Registry, and 297 patients were analysed for atrioventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…К таким критическим факторам относят: перенесенный инсульт, наличие фибрилляции предсердий, тромбофилию, тромбоэмболию легочной артерии в анамнезе, мигрень, занятие дайвингом (подводным плаванием), наличие синдрома платипноэ-ортодеоксии (одышка и низкая сатурация кислорода в вертикальном положении, но без симптомов в положении лежа) [36][37][38]. В настоящее время наиболее авторитетной в мире публикацией по данному направлению является SCAI (Society for Cardiovascular Angiography & Interventions) Guidelines for the Management of Patent Foramen Ovale (2019-2022) [39,40].…”
Section: таблица 1 возможные осложнения закрытия дефекта межпредсердн...unclassified
“…К таким критическим факторам относят: перенесенный инсульт, наличие фибрилляции предсердий, тромбофилию, тромбоэмболию легочной артерии в анамнезе, мигрень, занятие дайвингом (подводным плаванием), наличие синдрома платипноэ-ортодеоксии (одышка и низкая сатурация кислорода в вертикальном положении, но без симптомов в положении лежа) [36][37][38]. В настоящее время наиболее авторитетной в мире публикацией по данному направлению является SCAI (Society for Cardiovascular Angiography & Interventions) Guidelines for the Management of Patent Foramen Ovale (2019-2022) [39,40].…”
Section: таблица 1 возможные осложнения закрытия дефекта межпредсердн...unclassified
“…On the other hand, atrioventricular block post-transcatheter closure of ASD occurs in rare instances, and it can be transient or may progress to complete heart block [ 15 ]. When compared with patients with unclosed ASD, Albaek et al showed that those with interventional ASD closure were at higher risk of developing atrioventricular block, incomplete right bundle branch block, or left anterior fascicular block and had a higher demand for pacemaker implantation [ 16 ].…”
Section: Arrhythmias and Conduction Disorders Associated With Asdmentioning
confidence: 99%
“…Patients with repaired atrial septal defect (ASD) and atrioventricular septal defect (AVSD) are at increased risk of sinus node dysfunction and heart block, and pacemaker implantation is thus common [57,58]. CS anatomy is abnormal, and it is frequently absent or with atretic ostia [59].…”
Section: Lesion: Asd Avsd Repairsmentioning
confidence: 99%